Circadian rhythms and memory formation: regulation by chromatin remodeling - Sahar, Saurabh; Sassone-Corsi, Paolo (Frontiers in Molecular Neuroscience, 2012)
Epigenetic changes, such as DNA methylation or histone modification, can remodel the chromatin and regulate gene expression. Remodeling of chromatin provides an efficient mechanism of transducing signals, such as light or nutrient availability, to regulate gene expression. CLOCK:BMAL1 mediated activation of clock-controlled genes (CCGs) is coupled to circadian changes in histone modification at their promoters. Several chromatin modifiers, such as the deacetylases SIRT1 and HDAC3 or methyltransferase MLL1, have been shown to be recruited to the promoters of the CCGs in a circadian manner. Interestingly, the central element of the core clock machinery, the transcription factor CLOCK, also possesses histone acetyltransferase activity. Rhythmic expression of the CCGs is abolished in the absence of these chromatin modifiers. Recent research has demonstrated that chromatin remodeling is at the cross-roads of circadian rhythms and regulation of metabolism and aging. It would be of interest to identify if similar pathways exist in the epigenetic regulation of memory formation.